PENGARUH DISIPLIN DAN MOTIVASI TERHADAP KINERJA GURU DI SMP TAMAN DEWASA KOTA PROBOLINGGO - jurnalpps pps; Herlina Agus Verawati (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
The purpose of this study is to determine the effect of work discipline and work motivation on performance in the SMP Taman Dewasa in Probolinggo City. This research uses quantitative and takes a sample of 39 respondents, data collection methods using questionnaires and sampling techniques using census techniques. The analytical tool used was a questionnaire test consisting of a validity and reliability test, a classic assumption test, a multiple regression test, a determination test, a hypothesis test consisting of an F test, a t test and a dominant test. The results of the validity test show all valid question items above 0.316 and the results of the reliability test show the reliable results are above 0.60. Normality Test shows normally distributed data. Multicollinearity test shows the independent variable (X) and the dependent variable (Y) there is no correlation between the independent variables or the regression model free from multicollinearity. Heteroscedasticity test showed there was no heteroscedasticity. Autocorrelation test showed no autocorrelation. The t test showed that the work discipline variable (X1) had a partial effect.